Electrical characteristics of hierarchical conductive pathways in cementitious composites incorporating CNT and carbon fiber. (September 2017) - Kim, G.M.; Park, S.M.; Ryu, G.U.; Lee, H.K.
Abstract: Cementitious composites incorporating CNT and carbon fiber were produced in the present study, and the effect of the incorporation of carbon fiber on the electrical characteristics of the composites was investigated. Polycarboxylic acid based superplasticizer and silica fume were used to ensure the dispersion of the CNT and carbon fiber. Independent variables were the water to cement ratio, the amount of carbon fiber added to the composites. The test results showed that the cementitious composites incorporating CNT and carbon fiber had more stable electrical resistivity compared to those without carbon fiber. A microstructural analysis was conducted and the mechanism of the improved electrical characteristics of the cementitious composites incorporating CNT and carbon fiber was discussed.